قلق المستقبل و علاقته بقلق الامتحان لدى طلبة الجامعة - نملي، مصباح (جامعة الوادي university of Eloued, 2021)
الملخص: تعالج الدراسة الحالية موضوع قلق المستقبل وعلاقته بقلق الامتحان لدى طلبة جامعة حمه لخضر الوادي، خلال الموسم الدراسي 2020/2021 اعتمدت الدراسة على المنهج الوصفي الارتباطي، وذلك بإستخدام مقياس قلق المستقبل لـ: زينب محمود شقير (2005)؛ ومقياس قلق الإمتحان لـ (غربي عبد الناصر- 2015)، وقد تم التأكد من خصائصهما السيكومترية (الصدق، والثبات) على عينة قوامها (36) فردا، تم إختيارهم بطريقة عرضية. تم تطبيق الأدوات في صورتها النهائية على عينة عرضية تتكون من (50) فردا، وبعد جمع البيانات وتبويبها، تم معالجتها بالإستعانة بـ (20Spss )، وبإستخدام معامل الإرتباط بيرسون، توصلت الدراسة للنتائج التالية:  توجد علاقة ارتباطية ذات دلالة احصائية بين قلق المستقبل وقلق الاستعداد للامتحان لدى طلبة جامعة حمه لخضر الوادي.  لا توجد علاقة ارتباطية ذات دلالة احصائية بين قلق المستقبل وقلق أداء الامتحان لدى طلبة جامعة حمه لخضر الوادي.  لا توجد علاقة ارتباطية ذات دلالة احصائية بين قلق المستقبل وقلق الانتظار لنتيجة الامتحان لدى طلبة جامعة حمه لخضر الوادي. كما توصلت الدراسة في نتائجها الكلية الى انه:  لا توجد علاقة ارتباطية ذات دلالة احصائية بين قلق المستقبل وقلق الامتحان لدى طلبة الجامعة. Summary : انجليزية The study in-hand tackles the problem of test Future anxiety among University students Hamma Lakhdar El-oued province of Eloued during the 2020/2021. Scholar season. the research papers has been conducted following the relative descriptive method; using the models of measure Future anxiety for Zayneb Chakir (2005) in problem resolution and Gherbi AbdElnacer of test anxiety (2015), both models proved to be reliable and credible after a test on a 36 individuals sample, it was chosen vertically. After the data gathering and analysis process the final version of the tools was conducted on a horizontal sample of (50) indivuduals and after using a "Person" link multiplier, the results were as follows: - A statistical relative relation was found between Future anxiety and Anxiety about preparing for an exam among University students Hamma Lakhdar El-oued. - A statistical relative relation was found between Future anxiety and Exam performance anxiety among University students Hamma Lakhdar El-oued. - A statistical relative relation was found between Future anxiety and anxiety about waiting the exam rexult among University students Hamma Lakhdar El-oued. And were as: - A statistical relative relation was found between Future anxiety and anxiety the exam rexult among University students Hamma Lakhdar El-oued.
دراسة وصفية ارتباطية بجامعة الوادي
مذكرة ماستر علم الإجتماع تخصص تربية علم النفس المدرسي
Keywords: قلق المستقبل، قلق الإمتحان; anxiété future, anxiété des examens; future anxiety, exam anxiety